KONSEP PENDIDIKAN AKHLAK ANAK USIA SEKOLAH DASAR MENURUT IBNU MISKAWAIH (Telaah Kitab Tahdzib al-Akhlaq) - Anis Ridha Wardati (Program Studi PGMI STAI Al Falah Banjarbaru, 2019)
The study aims to find out the akhlaq education nature, education materials and methods for children, and its relevance to character building in Islamic elementary school according to Ibnu Miskwaih in his book Tahdzib al-Akhlaq. The study employs a qualitative descriptive approach with kinds of literature research design. The data collection is from some kinds of literature. The data analysis technique includes discussing, analyzing, classifying, and deep describing akhlaq education concept for children according to IbnuMiskawaihin his book Tahdzib al-Akhlak. The result shows that (1) the nature of akhlaq education for children according to IbnuMiskawaih is the education focuses on directing human behavior to do good deeds based on the religion and psychology to create a consciousness which spontaneously encourages to do a good behavior and become a well-mannered human, achieve the perfectness as human, and reach a true and perfect (al-sa’adah). (2) The akhlaq education materials for children according to Ibnu Miskawaih is essential education for the body and soul needs and also for the relationship among humans. To achieve the goal, it needs education methods such as natural,assistance, habitual, and punishment method and (3) The akhlaq education formulated by Ibnu Miskawaih is also relevant with Islamic elementary school education to correct students’ behavior which is not in line with the existing values in their daily life and to build a well-mannered human (insan kamil). Keywords: The concept of Akhlaq Education for Islamic elementary school students, Ibnu Miskawaih, Tahdzib al-Akhlaq.